PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR IPA PADA SISWA KELAS V SD LAB UNDIKSHA - Ni Nyoman Lisna Handayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This research aims to investigate the effect of cooperative learning model TGT type toward learning motivation and science learning outcome of fifth grade elementary school students in Batur cluster, Bangli. This research was a quasi-experiment with Posttest-Only Control-Group Design. Research population was 128 fifth grade elementary school students Batur Cluster. Sixty students were selected as sample using random sampling technique. Learning motivation data were gathered using questionnaire and science learning outcome data were collected used multiple choice test. Data were analyzed using MANOVA (Multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. Research results show that: First, learning motivation of students who followed TGT type of cooperative learning model was significantly better than students who followed conventional learning (F = 276.890; p < 0.05). Second, science learning outcome of students who followed TGT type of cooperative learning model was significantly better than students who followed conventional learning (F = 29.991; p < 0.05). Third, simultaneously, learning motivation and science learning outcome of students who followed TGT type of cooperative learning model was significantly better than students who followed conventional learning (F = 149.734; p < 0.05).